ANALISIS PENGGUNAAN TANDA BACA DALAM KARANGAN PADA PEMBELAJARAN TEMATIK KELAS V MADRASAH IBTIDAIYAH PERSATUAN UMMAT ISLAM MEKARJATI - Mardiatun Nisa; Henri Peranginangin Tanjung; Abdur Rahim (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2023)
Thematic subjects of Indonesian content are an integral part of the curriculum of Madrasah Ibtidaiyah Persatuan Ummat Islam (PUI) Mekarjati, Haurgeulis, Indramayu; which is scheduled/taught to students from the start of class V. The objectives of teaching this subject are, among other things, so that students understand and are skilled at using Indonesian, spoken and written, properly and correctly in accordance with the specified rules; including the use of punctuation marks. The purpose of the study was to determine (a) the level of understanding and ability of the fifth grade students of Madrasah Ibtidaiyah PUI Mekarjati, Haurgeulis, Indramayu using punctuation marks in written essays, and (b) the efforts of the teachers at Madrasah Ibtidaiyah PUI Mekarjati, Haurgeulis, Indramayu to improve students' understanding and abilities so that students do not make mistakes using punctuation marks in written essays. This research was conducted with a qualitative approach (case study) using the method of (a) interviewing researchers with teachers and related parties, (b) the practice of making Indonesian essays for 30 minutes by 13 students of class V Madrasah Ibtidaiyah PUI Mekarjati, Haurgeulis, Indramayu based on the assignment plan prepared by the class teacher. All the results of the practice of writing essays were then analyzed by researchers and teachers with a focus on evaluating the use of punctuation marks: period (.); commas (,); question mark (?), exclamation mark (!); and a dash (-). The results showed that (a) errors in the use of punctuation marks were 31 out of 12 students, (b) errors in using comma punctuation were 25 out of 11 students, (c) errors in the use of question marks were 7 out of 4 students, (d) errors in the use of punctuation marks. exclamation mark is 1 of 1 students, and (e) the error of using hyphen is 5 out of 2 students. As for the efforts of the Madrasah Ibtidaiyah teachers, PUI Mekarjati, Haurgeulis, Indramayu to improve students' understanding and abilities, namely by increasing the frequency of practice in making written essays using punctuation marks.